Comparative Epidemiology of Citrus tristeza virus in Plantings of Various Citrus Species in Costa Rica, and Long Distance Spread by the Brown Citrus Aphid - Gottwald, Timothy R. (2002)
Copyright 2002, International Organization of Citrus Virologists